Implementing the Principle of Good Governance in Villages from the Perspective of Village Law - Hayati, Siti Nur; Warjiyati, Sri; Al Maliki, Muhammad Alwi (Laboratorium Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya (https://uinsa.ac.id/fsh/facility), 2025)
This study explains that the implementation of good governance principles in village administration is a crucial foundation for establishing transparent, participatory, and accountable governance, while also promoting the integration of gender perspectives to achieve inclusive governance. The research analyzes the extent to which good governance principles have accommodated gender aspects in village governance policies and practices based on Law Number 6 of 2014 concerning Villages. This study employs a normative legal research method, using both statutory and conceptual approaches to analyze the application of good governance within the village governance system. The analysis primarily uses Law Number 6 of 2014 as the analytical tool. The findings reveal that good governance is a fundamental concept in establishing sound government. The principles of good governance, although unwritten, can in certain circumstances be drawn upon as applicable legal norms. When good governance is achieved, good government will follow. According to the Village Law, the application of good governance in the village governance system can be seen through implementing several principles, such as legal certainty, orderly administration, transparency, accountability, effectiveness, efficiency, public interest, local wisdom, and participation. However, alongside these opportunities, implementing good governance in village governance also faces various challenges. Opportunities include: a supportive legal and regulatory framework, the availability of village funds, a local culture that supports participation, and advances in information technology. The challenges include: limited human resource capacity, risks of corruption and abuse of power, low public participation, political interference and conflicts of interest, and unequal access to information technology.